1990
DOI: 10.1128/jb.172.4.1791-1797.1990
|View full text |Cite
|
Sign up to set email alerts
|

The HtrA (DegP) protein, essential for Escherichia coli survival at high temperatures, is an endopeptidase

Abstract: As a preliminary step in the understanding of the function of the Escherichia coli HtrA (DegP) protein, which is indispensable for bacterial survival only at elevated temperatures, the protein was purified and partially characterized. The HtrA protein was purified from cells carrying the htrA gene cloned into a multicopy plasmid, resulting in its overproduction. The sequence of the 13 N-terminal amino acids of the purified HtrA protein was determined and was identical to the one predicted for the mature HtrA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
272
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(292 citation statements)
references
References 26 publications
19
272
0
1
Order By: Relevance
“…2). Experimental studies have confirmed that HtrA is a serine protease -purified HtrA shows ATP-independent endopeptidase activity against beta-casein (but not against many other standard protease substrates) that can be inhibited by diisopropyl fluorophosphate, a specific inhibitor of serine proteases (Lipinska et al, 1990). Mutating two of the putative catalytic triad residues, Ser-210 and His-105, leads to a loss of protease activity (Skorko-Glonek et al, 1995a), with no detectable changes in secondary structure (Skorko-Glonek et al, 1995b).…”
Section: Amino Acid Sequencementioning
confidence: 96%
See 1 more Smart Citation
“…2). Experimental studies have confirmed that HtrA is a serine protease -purified HtrA shows ATP-independent endopeptidase activity against beta-casein (but not against many other standard protease substrates) that can be inhibited by diisopropyl fluorophosphate, a specific inhibitor of serine proteases (Lipinska et al, 1990). Mutating two of the putative catalytic triad residues, Ser-210 and His-105, leads to a loss of protease activity (Skorko-Glonek et al, 1995a), with no detectable changes in secondary structure (Skorko-Glonek et al, 1995b).…”
Section: Amino Acid Sequencementioning
confidence: 96%
“…Lipinska et al (1990) reported that HtrA, when overexpressed in E. coli, was partially degraded within cells to give two 43 kDa proteins that co-purified with the intact 48 kDa protein. Skorko-Glonek et al (1995a) showed that these breakdown products were the result of cutting after Cys-69 and Gln-82 of the mature protein.…”
Section: The Prpa and Prpb Phosphoprotein Phosphatasesmentioning
confidence: 99%
“…HtrA2) belongs to a family of serine proteases that is well conserved from bacteria to humans. 88 In bacteria, HtrA2 is localized within the periplasmic space and determines thermotolerance, 89 whereas in healthy eukaryotic cells Omi/HtrA2 is confined to the IMS. After MOMP, the protease is released into the cytosol and promotes apoptosis via caspase-dependent and -independent mechanisms.…”
Section: Vital Functions Of Mitochondrial Death Effectorsmentioning
confidence: 99%
“…The other strategy involved the characterization of a mutant which was defective in proteolysis of certain periplasmic fusion proteins (33). Subsequent studies verified that the product of the htrA gene is indeed an endopeptidase (21). Therefore, the product of the htrA gene is a periplasmic protease that is required only at elevated temperatures.…”
mentioning
confidence: 99%